Spontaneous Rupture of Rhabdomyosarcoma of the Testis With Unilateral Ptosis: A Case Report and Literature Review - Wu, Ronghua; Liu, Xing; Song, Yajun; Yi, Shanhong; Chen, Wei; Fu, Wanlei; Zhu, Jingzhen (Frontiers in Pediatrics, 2022)
Spontaneous rupture of testicular rhabdomyosarcoma is very rare. We report a case of spontaneous testicular rupture that was pathologically confirmed as rhabdomyosarcoma with unilateral blepharoptosis. The patient, a 19-year-old male, and his father had weakness of the left eyelid muscle. The patient was suspected to have a right inguinal hernia by a family doctor but was not treated further. Two days later, there was skin itching in the right inguinal area, with redness, swelling and discomfort of the right scrotum, and the patient went to the local hospital again. Ultrasound examination showed that a contusion of the right testis may have been complicated with orchitis. Oral levofloxacin was ineffective. The scrotal swelling had significantly increased. He came to the emergency room of our hospital and was treated with levofloxacin, but the pain was not relieved. CT and ultrasound examination could not identify the cause of the disease. Exploration of the right scrotum was performed under general anaesthesia and confirmed that the right testis had spontaneously ruptured. The pathological diagnosis was rhabdomyosarcoma of the right testis. Testicular rhabdomyosarcoma is clinically rare, and spontaneous rupture is even rarer. The pathogenesis of the disease needs to be further studied, and the diagnosis should be made on a case-by-case basis. Overall, the prognosis of testicular rhabdomyosarcoma is poor. As seen in this case, further study is required to determine whether there is some association between testicular rhabdomyosarcoma and ptosis. Unfortunately, the patient’s family rejected a genetic examination because of financial difficulty. We report only a single case of this rare phenomenon here.